KALENDER HIJRIAH KRITERIA 29 DALAM TINJAUAN FIKIH - Elly Uzlifah (ELFALAKY: Jurnal Ilmu Falak, 2022)
Criteria 29, ideas by Hendro Setyanto emerged as a new perspective criterion in the compilation and unification of the Hijri calendar in Indonesia which is still so thick of difference between the pattern of understanding mazhab hisab and mażhab rukyah. If the current criteria tries to approach the beginning of the month with visibility criteria of the hilal whose visibility condition is highly dependent on local conditions, then criterion 29 comes with a typical Indonesian tropical climate approach. The archipelagic environment in the equatorial region of Indonesia certainly has a difference in visibility with the desert environment where located in the subtropical region of Saudi Arabia, so the effort to apply the visibility criteria of a place to another certainly has a variety of different problems and constraints. Hijriah calendar countdown criteria 29 Astronomically is a pure argument which is argumentative with high accuracy computing method. The results showed that in Fiqh, the basic concepts of Hijri calendar criterion 29 in the determination of the beginning of the lunar month according to the jumhur view of the juris of Fiqh, while the recalculation of the Hijri calendar criteria 29 is one of the wasīlah option to simplify and controll calendar of rukyah. Regardless of the Hijri Islamic calendar, the criteria 29 gets a reasonable position, the rukyah is still declared as a standard (al-aṣl). []